Angiopoietin-2 stimulation of endothelial cells induces αvβ3 integrin internalization and degradation - Thomas, Markus; Felcht, Moritz; Kruse, Karoline; Kretschmer, Stella; Deppermann, Carleen; Biesdorf, Andreas; Rohr, Karl; Benest, Andrew V.; Fiedler, Ulrike; Augustin, Hellmut (The journal of biological chemistry, 2010)
The angiopoietins (Ang-1 and Ang-2) have been identified as agonistic and antagonistic ligands of the endothelial receptor tyrosine kinase Tie2, respectively. Both ligands have been demonstrated to induce translocation of Tie2 to cell-cell junctions. However, only Ang-1 induces Tie2-dependent Akt activation and subsequent survival signaling and endothelial quiescence. Ang-2 interferes negatively with Ang-1/Tie2 signaling, thereby antagonizing the Ang-1/Tie2 axis. Here, we show that both Ang-1 and Ang-2 recruit β3 integrins to Tie2. This co-localization is most prominent in cell-cell junctions. However, only Ang-2 stimulation resulted in complex formation among Tie2, αvβ3 integrin, and focal adhesion kinase as evidenced by co-immunoprecipitation experiments. Focal adhesion kinase was phosphorylated in the FAT domain at Ser910 upon Ang-2 stimulation and the adaptor proteins p130Cas and talin dissociated from αvβ3 integrin. The αvβ3 integrin was internalized, ubiquitinylated, and gated toward lysosomes. Taken together, the experiments define Tie2/αvβ3 integrin association-induced integrin internalization and degradation as mechanistic consequences of endothelial Ang-2 stimulation.
Gesehen am 15.11.2023